BLEACHING OF CRUDE PALM OIL BY ADSORPTION METHOD WITH USING NATURAL ZEOLITE FROM LAMPUNG - Widi Astuti; Muhammad Amin; Aprimal Aprimal (Jurnal Zeolit Indonesia, 2006)
The research about bleaching of crude palm oil by adsorption method with using natural zeolite from Lampung has been done. The experiment result shows that natural zeolite from Lampung can be used as adsorbent for bleaching process of crude palm oil. Zeolite had been activated by chemical method with hydrochloric acid (HCl) solution before it was used as adsorbent. From the experiment result, we know that the best condition for bleaching process are weight percentage of zeolite that was used to get the highest of transmittance is 20% and the best concentration of HCl solution is 4%. The highest of transmittance for this condition is 48.5.